Canadian Journal of Soil Science - Canadian Journal of Soil Science (Canadian Science Publishing, 2026)
Established in 1921, this journal is international in scope, publishing fundamental and applied research from all areas of soil science around the world. These areas include traditional soil biology, physics, and chemistry; pedology; use, management, and development; soil and environment interactions; land reclamation and contaminant remediation. It draws from and interfaces with numerous fields such as agriculture, agrometeorology, ecology, engineering, environmental science, environmental stewardship, forestry, geography, geology, hydrology, land rehabilitation, landscape processes, mapping and evaluation, microbiology, soil-plant interactions, and urban uses.
FI 0.42
Q4
Keywords: Life Sciences; Soil Sciences; Ciencias del suelo; Edafología; Acuerdos transformativos; Transformative agreements; Ciencia del suelo